10. Ventricular septal defect’s closure via right thoracotomy: Experiences with 100 consecutive cases from Vietnam National Children’s Hospital - Vinh, Tran Quang; Thao, Giang Thach; Mai, Nguyen Tuan; Chien, Nguyen Dinh; Hang, Nguyen Thi Thu; Truong, Nguyen Ly Thinh (Tạp chí Nghiên cứu Y học, 2023)
We evaluated the feasibility and effectiveness of the right vertical sub-axillary incision used for the closure of ventricular septal defect. 100 patients (55 males and 45 females) who consecutively underwent surgical repair of their ventricular septal defect at our institution from January 2020 to November 2021 were retrospectively reviewed. Technique considerations were right thoracotomy with a vertical mid-axillary line mini-incision, and central cannulation for cardiopulmonary bypass. Median age was 13 months; median weight was 8.7 kg. The mean cardiopulmonary bypass time and aortic cross-clamp time were 67 ± 16 minutes, 51 ± 15 minutes respectively. The ICU stay was 2.2 ± 1.2 days, mechanical ventilation time was 12.9 ± 28.2 hours, postoperative hospital stays was 9.9 ± 4.9 days. Morbidities were pneumonia (20%); surgical site infection (3%); subcutaneous emphysema (44%); transient arrythmias (10%). There was no conversion to another approach. There was no early or mid-terms mortality with a mean follow up of 15.8 ± 5.2 months. All patients are in a good health status. No significant residual defects were found on their last follow-up echocardiography. In conclusion, the ventricular septal defect’s closure via right thoracotomy at Vietnam National Children’s Hospital is a safe and feasible procedure with excellent cosmetic results.